Harmony of Religion, Identity, and Politics: The Phenomenon of Idolatry in Arkoun's Political Ethics Framework - Fakhruddin, M. Anas (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
This study explores the intricate relationship between religion, identity, and politics in the context of Indonesia's 2019 and 2024 presidential elections. The academic concern stems from increasing societal polarization, the rise of idolatrous voters, and the shallow use of religious narratives in political discourse. Using a qualitative approach and critical discourse analysis, this research investigates how identity politics, theological reasoning, and candidates’ rhetorical strategies shape voter behavior. Findings reveal that low levels of literacy and the dominance of religious symbolism foster irrational political choices and intensify social conflict. Drawing from Mohammed Arkoun's framework of political ethics, particularly his principles of liberative-transformation and religion-state relations, this study proposes strengthening critical reasoning and ethical political ideation. In conclusion, religion, identity, and politics are inseparable systems, best addressed through historical awareness, critical thought, and the formation of transformative agents.